Treatment of Acute Nonvariceal Upper Gastrointestinal Bleeding in Chinese Patients on Antithrombotic Therapy - Gao, Feng (Gastroenterol Res Pract, 2019)
OBJECTIVE: To assess the treatment of acute nonvariceal upper gastrointestinal bleeding (ANVUGIB) in Chinese patients on antithrombotic therapy. METHODS: The clinical data of patients with ANVUGIB who underwent upper gastrointestinal endoscopy 24 h after bleeding at Beijing Anzhen Hospital, Capital Medical University, from 2016 to 2018, were analyzed retrospectively. The patients were divided into antithrombotic therapy and control groups and into high-risk (Forrest Ia, Ib, IIa, and IIb) and low-risk (Forrest IIc and III) bleeding groups according to the results of endoscopy. RESULTS: In all, 230 patients were enrolled, with 99 cases in the antithrombotic group (antiplatelet therapy 80 patients, anticoagulant therapy 19 patients) and 131 cases in the control group (without antithrombotic therapy). A total of 78 and 21 and 84 and 47 patients were at high- and low- risk for bleeding (P = 0.019) in the antithrombotic and control groups, respectively; 12.1% and 4.6% had esophageal bleeding (P = 0.047), and 8 and 2 patients received interventional therapy (P = 0.021). Overall, 21 patients with hemodynamic instability were treated via endoscopy with anesthesia under tracheal intubation and ventilator support: 20 patients in the antithrombotic group (13 patients within 1 month after coronary intervention, 5 patients within 1 month of cardiac-valve replacement, and 2 patients within 4 years of cardiac-valve replacement) and 1 patient with third-degree atrioventricular block in the control group. Ten patients received interventional therapy: eight and two in the two groups, respectively. Multidisciplinary consultation was conducted to regulate the use of antithrombotic drugs. CONCLUSION: Compared to the controls, patients in the antithrombotic group had a significantly higher incidence of critical and active bleeding. Patients with hemodynamic instability should be examined and treated via upper gastrointestinal endoscopy under anesthesia with tracheal intubation and ventilator support.